WHAT ROLE FOR GOVERNMENT? THE PROMOTION OF CIVIL SOCIETY THROUGH FORESTRY‐RELATED CLIMATE CHANGE INTERVENTIONS IN POST‐CONFLICT NEPAL. (8th September 2014) - Rutt, Rebecca Leigh; Lund, Jens Friis
SUMMARY This study examines rationales behind the choice of local interlocutors by forestry‐related climate change projects in post‐conflict Nepal. In their stated objectives, all projects claim to involve the government, and most project decision makers are in favor of government involvement, yet project resources overwhelmingly favor civil society institutions. Project decision makers' choices are shaped by a combination of donor conditionalities, contextual constraints, and beliefs about which institutional attributes matter and how to address historical marginalization. The projects' empowerment of civil society sidesteps opportunities to strengthen the local government, which is described as weak, disinterested, and lacking legitimacy owing to the absence of elections due to the unsettled post‐conflict situation. Through the choices made and their justifications, projects and donors further marginalize the local government materially and discursively and thereby entrench its perceived deficiencies. We argue that this privileging of civil society may have implications for government legitimacy and post‐conflict reconstruction and call for donors and the intervening institutions they fund to critically and collectively reassess the role of forestry‐related climate change projects in the larger process of post‐conflict reconstruction in Nepal. Copyright © 2014 John Wiley & Sons, Ltd.